Analysis of Employee Performance at the Fisheries Office of Badung Regency - Ngakan Made Agus Widiartha; Ni Putu Tirka Widanti; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The performance of government agency employees is a result of work that is strongly linked to the agency's strategic goals, customer satisfaction, and contribution to the economy. Problems encountered include under-target program and activity implementation. The purpose of this study was to determine the reasons, inhibiting factors, and solutions to improve employee performance. This study used a qualitative descriptive approach. The results showed that employee performance at the Badung Regency Fisheries Office, based on indicators of responsiveness, responsibility, and accountability, was good, but productivity and service quality indicators were not yet optimal. Inhibiting factors for improving employee performance include a lack of employee interest and opportunities to participate in technical training in accordance with competencies, limited rotation between fields, inadequate communication between leaders and staff, a lack of competent human resources, and inadequate facilities and infrastructure. Solutions to overcome obstacles to employee performance include supporting the implementation of program activities so that they are realized as planned, facilitating employee competency development, building better communication, providing a budget for inadequate facilities and infrastructure, and proposing additional staff with specialized expertise in fish farming. Keywords: Analysis, Employee Performance, Human Resources (HR)